The hungarian language in education in Ukraine - Csernicsko Istvan; Oros Ildiko; Csernicskó István; Orosz Ildikó; Черничко Степан; Орос Ільдіко (Mercator European Research Centre on Multilingualism and Language Learning, 2019)
Abstract. The Hungarian language belongs to the Finno-Ugric branch of the Uralic language family. The majority of native Hungarian speakers live in the Carpathian Basin in Hungary and in the neighbouring states. Since all the neighbouring languages belong to the Indo-European language family, Hungarian is very different from these languages, both genetically and typologically. The spoken and written variants of the Hungarian language in Ukraine belong to the dialect region underlying the Standard Hungarian Dialect. The Hungarian community living on the territory of the presentday Ukraine has been in a minority position since reaching agreements to bring the First World War to an end (except for a short period between 1938 and 1944 (Csernicskó & Ferenc, 2014: Csernicskó & Laihonen, 2016)). The effects of language contact between Hungarian and Ukrainian were visible at all levels of the linguistic system (Csernicskó & Fenyvesi, 2000; Csernicskó & Fenyvesi, 2012). Language contact is manifested primarily in verbal communication and less in written communication. The differences between Standard Hungarian and the UkrainianHungarian variety, however, do not interfere with communication: the Ukrainian Hungarians can easily understand Standard Hungarian. Likewise, for Hungarians living in other countries, it is easy to understand the Ukrainian variants of the Hungarian language. The Standard Hungarian Dialect is used in education institutions with Hungarian as the medium of instruction.
http://real.mtak.hu/104892/
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00007766
Keywords: Hungarian language; Ukraine; education